Developing knowledge and capacity for innovation in food and agriculture: KCID division brochure - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
The Knowledge, Capacity, and Innovation Division (formerly ISNAR) works to improve the functioning of food and agriculture systems by facilitating knowledge management—the creation, accumulation, sharing, and utilization of knowledge—and developing the capacity for innovation by all actors along the food and agriculture value chain. Fostering innovation means investing in agricultural science and technology, research and extension, education and training, and farmer organizations and other local institutions. The division strengthens the capacity of organizations and individuals involved in generating and disseminating new knowledge, producing the next cadre of actors in the food and agriculture value chain, and organizing the creation and marketing of agricultural products. In combination with indigenous knowledge, new findings, and technology, the division uses appropriate institutional and policy arrangements to promote increased productivity and competitiveness of agriculture and to improve the livelihoods of smallholder operators in rural areas of developing countries.